2020
DOI: 10.1111/apt.15751
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcome of patients with acute severe ulcerative colitis responding to intravenous steroids

Abstract: Background:The long-term outcome of patients with acute severe ulcerative colitis (ASUC) responding to intravenous steroids (IVS) has been poorly reported. Aims:To assess relapse-free survival in patients with ASUC responding to IVS. Methods:Between January 2006 and December 2017, 142 consecutive patients with ASUC (according to modified Truelove-and-Witts criteria) responding to IVS were included in this multicentre retrospective study. Relapse was defined by a partial Mayo Clinic score >4 and/or the need for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 28 publications
1
23
2
Order By: Relevance
“…Moreover, mean hemoglobin value of the study population of Salameh et al was 11.3 ± 2.0 g/dL. 1 We found that haemoglobin levels lower than 11.8 g/dL predicted lack of response to IV steroids in ASUC. 2 Despite the advent of biologic therapies, ASUC requiring hospitalisation and IV steroids is still a risk factor for early and late colectomy.…”
Section: Letter: Long-term Outcomes Of Patients With Acute Severe Ulcmentioning
confidence: 44%
See 3 more Smart Citations
“…Moreover, mean hemoglobin value of the study population of Salameh et al was 11.3 ± 2.0 g/dL. 1 We found that haemoglobin levels lower than 11.8 g/dL predicted lack of response to IV steroids in ASUC. 2 Despite the advent of biologic therapies, ASUC requiring hospitalisation and IV steroids is still a risk factor for early and late colectomy.…”
Section: Letter: Long-term Outcomes Of Patients With Acute Severe Ulcmentioning
confidence: 44%
“…14.5% of our patients had colectomy during the follow-up period of 4.4 years [1.1-10 years] 2 ; and 15% of complete responders were operated on over the following decade according to Bojic et al5 ).In our cohort, 89% of patients who underwent colectomy had been on immunosuppressant treatment, 2 while Salameh et al reported that 61.7% of relapsing patients received immunomodulators 1. This suggests that immunomodulatory treatment is not very effective for maintenance therapy after ASUC.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…We thank Fabián et al for their interest in our work and appreciate their positive comments 1 . We recently reported a high rate of relapse in patients with acute severe ulcerative colitis (ASUC) responding to intravenous steroids 2 . In this retrospective multicentre cohort study, the risk of relapse was lower in those treated with anti‐TNF maintenance therapy.…”
mentioning
confidence: 99%